Análisis del desempeño de la red de acceso de cobre considerando la tasa de transferencia de datos en sectores rurales - Imba Chontasi, Diego Alcides (2020)
At present, telecommunications in Ecuador, telecommunications make it easier for people to have access to all kinds of information and digital services. The Universal Service Plan constitutes a main strategy to eliminate the gaps that exist in the Ecuadorian population to access TIC (Mintel 2018). Article 89 of the Magna Carta indicates that the Universal Service constitutes the obligation to extend a defined set of telecommunications services to all inhabitants of the national territory with minimum conditions of accessibility, quality and fair prices, regardless of conditions economic, social or geographic location of the population (Mintel, 2018). In rural sectors one of the biggest problems in guaranteeing data transmission service has always been the availability of access or last mile. In Ecuador there are three fixed telephone providers with coverage in the main cities that are: CNT E.P, ETAPA E.P, SETEL S.A (ARCOTEL, 2018). The purpose of this project is to analyze the performance of the copper access network, considering the data transfer rate in rural sectors and propose a solution to the problem. For which practical experiments will be carried out in the field in the Pedro Moncayo Canton, Tabacundo Parish, in the community of Picalquí, in which maximum distances will be determined for different transfer rates offered by the provider, a solution will also be proposed to solve the problem found.